Effects and mechanisms of gastric electrical stimulation on visceral pain in a rodent model of gastric hyperalgesia secondary to chemically induced mucosal ulceration. Issue 2 (25th October 2013) - Sun, Y.; Tan, Y.; Song, G.; Chen, J. D. Z.
Abstract Background Gastric electrical stimulation (GES) has been suggested as a potential treatment for patients with gastric motility disorders. The aim of this study was to examine the effects and mechanisms of GES on visceral pain in awaken rats. Methods Under anesthesia, acetic acid was injected into the submucosal layer of the stomach wall in Sprague–Dawley (SD) male rats. Each rat was chronically placed with an intragastric balloon and two pairs of electrodes on gastric serosa for GES and at the neck muscles for electromyography (EMG) recordings respectively. The study was composed of four experiments. Exp 1 was designed to determine optimal GES parameters in reducing EMG response to gastric distention (GD). Exp 2 was performed to investigate the effect of GES on gastric tone/accommodation. Exp 3 was to investigate if the opioid pathway was involved in the analgesic effects of GES. Exp 4 was to assess the effectiveness of GES on the spinal cord neurons (T9‐T10) responding to GD. Key Results (i) Gastric electrical stimulation with a train on of 0.1 s and off of 0.4 s, 0.25 ms, 100 Hz, and 6 mA significantly reduced GD‐induced EMG responses at GD 40, 60, and 80 mmHg. (ii) The inhibitory effects of GES on the GD‐induced EMG responses were blocked by Naloxone. (iii) GES inhibited 90% of high‐threshold (HT) spinal neurons in response to GD. However, GES with the same parameters only suppressed 36.3% low‐threshold (LT) neuronal response to GD. Conclusions & Inferences Gastric electrical stimulation with optimal parameters inhibits visceral pain; the analgesic effect of GES on visceral pain is mediated via the endogenous opioid system and the suppression of spinal afferent neuronal activities.